Teknologi Terbaru Penanggulangan Badan Jalan Longsor dengan Konstruksi Sheetpile Berjoint - Karminto, Karminto (Syntax Literate, 2026)
The purpose of discovering the latest technology in the field of retaining walls is to effectively overcome the problem of subsidence and landslides on the road body located in the Cendana Resident 2 Housing Complex, Jalan Masjid, Ciateur Village, Serpong District, South Tangerang. The main problem found in the field is the occurrence of subsidence and landslides. The problem in the field is the narrow road leading to the project with a road width of only 2 meters, so it is necessary to think about an accountable and permanent solution, for that must be used reliable methods and capable construction technology to overcome these problems. This technology has never been used before, namely Flat Berjoint Sheetpile Construction. With the latest and newest technology, it is hoped that it can answer these geotechnical problems. In the future, this activity can encourage an increase in the quality of construction project implementation in Indonesia and expand the adoption of modern construction technology that is more sustainable and green construction.